2000
DOI: 10.1128/jb.182.24.7029-7034.2000
|View full text |Cite
|
Sign up to set email alerts
|

Regulatable Arabinose-Inducible Gene Expression System with Consistent Control in All Cells of a Culture

Abstract: The arabinose-inducible promoter P BAD is subject to all-or-none induction, in which intermediate concentrations of arabinose give rise to subpopulations of cells that are fully induced and uninduced. To construct a host-vector expression system with regulatable control in a homogeneous population of cells, the araE gene of Escherichia coli was cloned into an RSF1010-derived plasmid under control of the isopropyl-␤-D-thiogalactopyranoside-inducible P tac and P taclac promoters. This gene encodes the low-affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
146
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(158 citation statements)
references
References 17 publications
9
146
1
Order By: Relevance
“…In an effort to more easily predict pump physicochemical properties from fitness in selective environments, we removed these regulatory dynamics by TetR. Here, tet(B) is expressed by the arabinose‐inducible, glucose‐repressible promoter, pBAD, where we use a saturating arabinose concentration to obtain a largely homogeneous cellular population expressing tet(B) (Khlebnikov et al , 2000). We ensured moderate translational expression of TetB by engineering a ribosome binding site (RBS) sequence that provided measurable resistance at minimal fitness cost (Materials and Methods; Salis et al , 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In an effort to more easily predict pump physicochemical properties from fitness in selective environments, we removed these regulatory dynamics by TetR. Here, tet(B) is expressed by the arabinose‐inducible, glucose‐repressible promoter, pBAD, where we use a saturating arabinose concentration to obtain a largely homogeneous cellular population expressing tet(B) (Khlebnikov et al , 2000). We ensured moderate translational expression of TetB by engineering a ribosome binding site (RBS) sequence that provided measurable resistance at minimal fitness cost (Materials and Methods; Salis et al , 2009).…”
Section: Resultsmentioning
confidence: 99%
“…KHLEBNIKOV and OTHERS than varying the level of gene expression in individual cells of the culture, the concentration of arabinose in the medium changes the fraction of cells that are fully induced. Recently, we showed that expression of araE from an arabinose-independent (IPTG-inducible) promoter allows regulatable gene expression control from P BAD in individual cells (Khlebnikov et al, 2000). In this paper we show that expression of araE from constitutive promoters of various strengths on medium-copy plasmids or on the chromosome allows homogeneous expression from P BAD and that the level of araE expression affects the level of expression from P BAD at a given inducer concentration.…”
Section: Introductionmentioning
confidence: 91%
“…In both prokaryotes and eukaryotes, a number of wild-type regulatory circuits that have been analyzed at the singlecell level have been shown to exhibit discrete control (5,9,18,25,28,34,43,48). In addition, modified or synthetic circuits with either discrete or continuous control have been constructed (7,21,27,40). Wild-type circuits that exhibit continuous control of transcription in single cells, on the other hand, are less well studied, although recently two examples in yeast have been described (9,37).…”
mentioning
confidence: 99%